AGE-ASSOCIATED CHANGES IN SDF-1 TARGETING MIRNAS 29B-1-5P AND 141-3P ARE LINKED TO KYNURENINE LEVELS IN MSCS - Elmansi, A (Innov Aging, 2018)
We have identified a number of miRNAs that increase with age in human and murine bone marrow-derived mesenchymal stem cells (BMSCs). These miRNAs target a number of osteogenic gene families including the Stromal cell-derived factor-1 (SDF-1α /CXCL12) axis. Two of these SDF-1 targeting miRNAs are also under estrogen suppression: miR-29b-1-5p (normally the 29b-1 passenger strand) and miR-141-3p. Of interest, high levels of kynurenine (KYN), a Tryptophan (Trp) metabolite generated by Indoleamine-(2,3)-dioxygenase (IDO1), have been linked to age-associated diseases, including osteoporosis. We tested the hypothesis that KYN increased the miR-29b-1-5p and miR-141-3p levels in BMSCs targeting the SDF-1 axis and other osteogenic genes. We show that KYN increases both miRNAs in a dose dependent fashion and decreases SDF-1 expression. Use of antagomirs to the miRNAs rescued SDF-1 expression levels, as did inhibition of the KYN receptor aryl hydrocarbon receptor (Ahr) with CH223191. Of interest miR-29b-1-5p also targets Hdac3, which is critical in the BMSC osteogenic versus adipogenic cell fate switch. Increasing KYN levels in BMSCs reduces osteogenesis, increases lipid pathways while reducing both SDF-1 and Hdac3. These results suggest that elevated levels of KYN might contribute to age related bone loss by attenuating levels of SDF-1α in BMSCs via up-regulation of the miRNAs 29b-1-5p and 141-3p. Further, that this increase in anti-osteogenic miRNAs is mediated by KYN signaling via an AhR transcription factor dependent pathway in BMSCs.